A Comparative Study of Two Temperature Interpolation Methods: A Case Study of the Middle East of Qilian Mountain. Issue 7 (March 2020) - Shan, Tong; Guangchao, Cao; Zhen, Chen; Fang, Liu; Meiliang, Zhao
Abstract: Background, aim, and scope The Middle East section of Qilian Mountain was used as the study area, and the temperature interpolation method based on DEM was compared. Materials and methods The temperature average correction method and Anusplin method were used to interpolate the monthly average temperature, seasonal average temperature and annual average temperature of 13 meteorological stations in the study area, and the average absolute error and root mean square error were determined by cross-validation method. The absolute value of the coefficient and index difference evaluates the verification site interpolation results. Results (1) The average absolute error and root mean square error of the vertical temperature correction method ranged from 0.07 °C to 1.36 °C and 0.09 °C to 1.65 °C, and the range of Anusplin ranged from 0.16 °C to 1.3 °C and 0.24 °C. -1.49 °C; (2) Anusplin and temperature vertical correction method on the average absolute error and root mean square error index, the absolute difference between the low temperature season index is 0.09 °C and 0.00 °C, respectively, the high temperature season is 0.30 °C and 0.32 °C. Conclusion The temperature vertical correction method is superior to Anusplin in MAE, RMSE and R 2 in July, August and September; the accuracy of temperature vertical correction in summer and autumn is higher than that of Anusplin, and Anusplin is more It is suitable for interpolation in low temperature season, and the vertical temperature correction method is more suitable for interpolation in high temperature season; the error of the two interpolation methods on the annual scale is larger, and the accuracy of temperature and temperature interpolation of Anusplin is much higher than the vertical correction method of temperature. Recommendations and perspectives Different interpolation methods are applicable to different regions, and there is no method that is absolutely suitable for the study area, and only a method that is relatively suitable for the study area. In general, the Anusplim method is more accurate than the temperature vertical correction method for the temperature of the Middle East in Qilian. The former is more suitable for the interpolation of temperature in the study area.